Stability enhancement of Cu2S against Cu vacancy formation by Ag alloying. (27th March 2018) - Barman, Sajib K; Huda, Muhammad N
Abstract: As a potential solar absorber material, Cu2 S has proved its importance in the field of renewable energy. However, almost all the known minerals of Cu2 S suffer from spontaneous Cu vacancy formation in the structure. The Cu vacancy formation causes the structure to possess very high p-type doping that leads the material to behave as a degenerate semiconductor. This vacancy formation tendency is a major obstacle for this material in this regard. A relatively new predicted phase of Cu2 S which has an acanthite-like structure was found to be preferable than the well-known low chalcocite Cu2 S. However, the Cu-vacancy formation tendency in this phase remained similar. We have found that alloying silver with this structure can help to reduce Cu vacancy formation tendency without altering its electronic property. The band gap of silver alloyed structure is higher than pristine acanthite Cu2 S. In addition, Cu diffusion in the structure can be reduced with Ag doped in Cu sites. In this study, a systematic approach is presented within the density functional theory framework to study Cu vacancy formation tendency and diffusion in silver alloyed acanthite Cu2 S, and proposed a possible route to stabilize Cu2 S against Cu vacancy formations by alloying it with Ag.